2015
DOI: 10.1002/ejoc.201501030
|View full text |Cite
|
Sign up to set email alerts
|

Pd/C‐Catalyzed Alkylation of Heterocyclic Nucleophiles with Alcohols through the “Borrowing Hydrogen” Process

Abstract: Although amyloid fibrils are associated with numerous pathologies, their conformational stability remains largely unclear. Herein, we probe the thermal stability of various amyloid fibrils. α‐Synuclein fibrils cold‐denatured to monomers at 0–20 °C and heat‐denatured at 60–110 °C. Meanwhile, the fibrils of β2‐microglobulin, Alzheimer’s Aβ1‐40/Aβ1‐42 peptides, and insulin exhibited only heat denaturation, although they showed a decrease in stability at low temperature. A comparison of structural parameters with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Besides, it was possible to carry out the process at lower temperatures. 319,320 In a recent and interesting approach, the preparation of a DMF-stabilized iridium nanocluster as methylation catalyst has been described. The corresponding micrographs of HR-TEM showed that the small Ir clusters had an average diameter of 1− 1.5 nm and were stabilized with DMF.…”
Section: Activation Of Alcoholsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it was possible to carry out the process at lower temperatures. 319,320 In a recent and interesting approach, the preparation of a DMF-stabilized iridium nanocluster as methylation catalyst has been described. The corresponding micrographs of HR-TEM showed that the small Ir clusters had an average diameter of 1− 1.5 nm and were stabilized with DMF.…”
Section: Activation Of Alcoholsmentioning
confidence: 99%
“…Furthermore, the catalyst could be recycled up to five times with a negligible loss of efficiency ( Figure 10). 320 3. (209) in the presence of Ni nanoparticles.…”
Section: Activation Of Alcoholsmentioning
confidence: 99%
“…For instance, Ohta et al reported the Pd/C‐catalyzed alkylation of heterocyclic nucleophiles with various alcohols, via the ‘borrowing‐hydrogen’ reaction in 1,4‐dioxane at 120 °C [Eq. (64)] . Additionally, 4‐hydroxy‐1‐methylquinolinone, barbituric acids, and oxindole are also suitable for this alkylation reaction.…”
Section: Applications Of Pd/cmentioning
confidence: 99%
“…7 Furthermore, Madsen et al and Hong et al reported Ru-NHC catalyzed direct amide syntheses using alcohols and amines. Very limited reports exist for the α-alkylation of amides 8 catalyzed by air sensitive cooperative pincer-type complexes.…”
Section: Introductionmentioning
confidence: 99%